The predator state. How conservatives abandoned the free market and why liberals should too - Galbraith, James K. 1908-2006
This is political economy at its best, in the tradition of Veblen?s Theory of the Leisure Class, or J.K. Galbraith?s The New Industrial State. The comparators are chosen carefully, for not only is The Predator State an update, it is equally as deserving of status as a classic. The issues are carefully examined, the prose is delightful, the arguments appear unassailable, and the choir?including this reviewer and presumably most of the readers of this journal?shouts ?Amen!?. But will the book be read? Can any book today capture the attention accorded to Veblen a century ago, or to Galbraith, senior, nearly fifty years ago? Still, one must applaud Jamie for trying. This is an amazing effort... The general theses can be simply stated. First, while conservatives toyed with laissez-faire, they quickly abandoned it in all important areas of policy-making. For them, it now serves as nothing more than an enabling myth, used to hide the true nature of our world. Ironically, only the progressive still takes the call for ?market solutions? seriously, and this is the major barrier to formulating sensible policy. Second, the ?industrial state? has been replaced by a predator state, a coalition of relentless opponents of the very idea of a ?public interest?, whose purpose is to master the state structure in order to empower a high plutocracy with nothing more than vile and rapacious goals. Finally, the ?corporate republic? created by the likes of Dick Cheney is highly unstable, a formula for national failure. Progressives must wrest control from the reactionaries before it is too late for restoration of America as the world?s financial anchor, technological leader, and promoter of collective security. Jamie thus resurrects both the extreme pessimism of Veblen?s notion of predation (by the conspicuously consuming leisure class in Veblen?s day, but by the corporate elite and Cheney?s imperial court today) as well as his only partially defined but optimistic vision of a world dominated by the engineers. As Jamie argues, his father admired Veblen but was most influenced by the New Deal, the mobilization during WWII, and the rise of the modern corporation that cooperated with government and labor to create the planned economy of the postwar period. Hence, Veblen?s opposition of the business enterprise versus the public interest was replaced by countervailing powers that compromised a largely acceptable truce. Jamie insists that his father?s analysis was correct, however, it was already becoming outdated by the early 1970s as the Bretton Woods system fell apart. The free market reactionaries promised that some combination of monetarism, supply side economics, balanced budgets, and free trade was the solution to America?s woes. The mantra ?free markets? provided an easy antidote to ?planning? that was said to constrain recovery and growth. As each conservative policy was tried, however, it resulted in obvious and even spectacular failure. In truth, all economies are always and everywhere planned?for the simple reason that planning is the use of today?s resources to meet tomorrow?s needs, something that all societies must do if they are going to survive?so the only question is who is going to do the planning, and to whom are the benefits going to flow? There are still a few true believers (principled conservatives that Jamie compares to noble savages in the political wilderness), but most conservatives realized that there is no conflict between ?big government? and ?the market? as they abandoned the myth but usurped the ?free market? label. All we are left with is the liberal who embraces the myth out of fear of being exposed as a heretic, a socialist, or a fool. Thus, the liberal pines to ?make the market work better?, never challenging the view (abandoned by all but the most foolish conservatives) that government is the problem. Economic freedom is reduced to the freedom to shop, including the freedom to buy elections, and anything that interferes is a threat. ?Market? means nothing more than ?nonstate?, a negation of use of policy in the public interest. Jamie provides a careful analysis of the frontline battles on many of the most important issues--Social Security, health care, inequality, immigration, security after 9-11, trade and outsourcing, and global warming?showing how ?market solutions? are designed to enrich a favored oligarchy through a spoils system administered through the state?s structure. The policy ?mistakes? in Iraq or New Orleans or at Bear-Stearns do not result from incompetence?indeed they only appear to be failures because we apply inappropriate measures of success. There is no common good, no public purpose, no shareholder?s interest; we are the prey and governments as well as corporations are run by and for predators. The ?failures? enrich the proper beneficiaries even as they ?prove? government is no solution. There is a way out, but it is not easy. Historically, regulation and standards have required acceptance by progressive business?those firms that recognized they would lose in races to the bottom. Today, corporate and public policy alike are run by the most reactionary elements, well-paid rogues that suck capacity. Wherever one finds a sector that still operates reasonably well, one finds remnants of New Deal institutions that support, guarantee, regulate, and leverage private activities, in spheres as diverse as higher education, housing, pensions, healthcare, the military-industrial complex (and the prison-industrial complex). Naturally, even these sectors are endangered as they represent potential riches (witness subprimes, a privatization mess that Wall Street would love to repeat with Social Security). Still, Jamie is hopeful. The ideology of free markets is bankrupt, but the US is not. The path is clear: re-regulation, planning, standards (including wage controls), and coming to grips with the nation?s global responsibilities.